Family Adaptation to Stroke: A Metasynthesis of Qualitative Research based on Double ABCX Model - Ali Hesamzadeh, RN, PhD Student of Nursing; Asghar Dalvandi, RN, PhD; Sadat Bagher Maddah, RN, PhD; Masoud Fallahi Khoshknab, RN, PhD; Fazlollah Ahmadi, RN, PhD (Asian Nursing Research, 2015)
Purpose: There is growing interest in synthesizing qualitative research. Stroke is a very common cause of disability often leaving stroke survivors dependent on their family. This study reports an interpretive review of research into subjective experience of families with stroke survivors based on the components of the Double ABCX Model including stressors, resources, perception, coping strategies, and adaptation of these families. Methods: Metasynthesis was applied to review qualitative research looking at stroke family members' experiences and responses to having a stroke survivor as a family member. Electronic database from 1990 to 2013 were searched and 18 separate studies were identified. Each study was evaluated using methodological criteria to provide a context for interpretation of substantive findings. Principal findings were extracted and synthesized under the Double ABCX Model elements. Results: Loss of independence and uncertainty (as stressors), struggling with new phase of life (as perception), refocusing time and energy on elements of recovery process (as coping strategy), combined resources including personal, internal and external family support (as resources), and striking a balance (as adaptation) were identified as main categories. Family members of stroke survivor respond cognitively and practically and attempt to keep a balance between survivor's and their own everyday lives. Conclusions: The results of the study are in conformity with the tenets of the Double ABCX Model. Family adaptation is a dynamic process and the present study findings provide rich information on proper assessment and intervention to the practitioners working with families of stroke survivors.